Implementasi pembelajaran toilet training dalam menumbuhkan kemandirian anak usia dini: Implementasi pembelajaran toilet training dalam menumbuhkan kemandirian anak usia dini - Efendi, Rivan Mutiasari; Afandi, Nur Kholik (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2024)
This research focuses on early childhood independence learning through toilet training at PAUD Cakrawala Kaki Langit. The background emphasizes the importance of developing children's independence from an early age to achieve the goals of early childhood education in accordance with Law Number 20 of 2003. Toilet training involves fostering children’s autonomy through a structured learning process so they are able to urinate and defecate. The child's independence phase can be carried out starting from the age of 2-4 years. Independence is the ability that children have and can do without the help of others, having self-confidence and discipline. Early childhood independence is greatly influenced by the family and school environment. The aim of this research is to observe the implementation of toilet training learning in fostering independence in young children. The type of research used by this researcher is descriptive qualitative research carried out using interview, observation and documentation methods. The principal and teacher of the Skyline Cakrawala preschool are the subjects that will be observed in the research. The research results show that toilet training is effective in training children's independence which includes discipline, responsibility, courage and motor skills. The storytelling method using pictorial media in this activity involves children and provides guidance on what steps to take when in the bathroom. Interviews with school principals and graphs confirm that children's independence shows good results where children are independent to go to the toilet themselves. The conclusion of this research is that children show significant independent abilities, including going to the toilet on their own, taking off and putting on pants, cleaning the toilet, washing vital organs, and washing their hands. The development of children's independence develops very well in accordance with the desired expectations from the various aspects assessed.